1978
DOI: 10.1073/pnas.75.3.1329
|View full text |Cite
|
Sign up to set email alerts
|

Composition of vacuoles and sarcoplasmic reticulum in fatigued muscle: electron probe analysis.

Abstract: Electron probe analysis, cryo-ultramicrotomy, and freeze-substitution were used to determine the nature of vacuolation and the subcellular composition in fatigued frog skeletal muscle fibers. The vacuoles caused by fatigue were part of the T-tubule system and contained high concentrations of NaC1. The calcium concentration in the terminal cisternae was higher than previously measured normal resting values. Mitochondrial calcium content was relatively low (mean i SEM, 2 h 2 mmol/kg dry weight). Fiber NaCl was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
3

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 22 publications
7
58
3
Order By: Relevance
“…With continuous stimulation at 1 Hz for 2-4 h, fast-twitch rat muscles increase their Ca 2ϩ content to ϳ2.5 times the endogenous level, whereas slow-twitch muscle shows little increase (183), consistent with the endogenous Ca 2ϩ and maximum SR capacity observed in such muscle types (176,440). Frog muscle fibers stimulated in vitro to fatigue increased SR Ca 2ϩ content by ϳ10% (190). In contrast, fast-and slow-twitch muscle stimulated in situ in the rat with intermittent 100-Hz tetani for 5 min showed an ϳ40% decline in total Ca 2ϩ content (286).…”
Section: Sr Camentioning
confidence: 62%
See 1 more Smart Citation
“…With continuous stimulation at 1 Hz for 2-4 h, fast-twitch rat muscles increase their Ca 2ϩ content to ϳ2.5 times the endogenous level, whereas slow-twitch muscle shows little increase (183), consistent with the endogenous Ca 2ϩ and maximum SR capacity observed in such muscle types (176,440). Frog muscle fibers stimulated in vitro to fatigue increased SR Ca 2ϩ content by ϳ10% (190). In contrast, fast-and slow-twitch muscle stimulated in situ in the rat with intermittent 100-Hz tetani for 5 min showed an ϳ40% decline in total Ca 2ϩ content (286).…”
Section: Sr Camentioning
confidence: 62%
“…It has been frequently suggested that Ca 2ϩ uptake by the mitochondria may play a significant role in overall Ca 2ϩ movements in a fiber, particularly those mitochondria situated close to the SR (223,401), with the effect possibly being more important in frog fibers than in mammalian fibers (68,270). However, the mitochondria do not contain high-capacity Ca 2ϩ binding proteins such as calsequestrin, and the absolute amount of Ca 2ϩ contained within the mitochondria in frog fibers at rest, or after stimulation by either a single tetanus or to fatigue, is Ͻ2% of that contained within the SR (190,408). In humans exercising for 1 h, the amount of Ca 2ϩ in the mitochondria only increased by ϳ50% above the level in rested muscle (297).…”
Section: Mitochondrial Ca 2؉ Handlingmentioning
confidence: 99%
“…These findings are noted to discuss in more detail the cause of muscle fatigue, which is regarded as the inhibition of E-C coupling. SOMLYO et al (1978) and GoNZALEZ-SERRATOS et al (1978) reported that the amount of the stored calcium in sarcoplasmic reticulum (SR) of fatigued muscle fiber is not different from that of normal muscle fiber. In the present experiment, the peak tension of contractures induced by 3 and 5 mM caffeine in the presence of subthreshold concentration of K+ (25 mM) or 0.01 % Triton X-100 in fatigued muscle fiber was not different from that of control caffeine contractures in normal muscle fiber (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it is not known whether or how the cis-trans polarity of vesicles incorporated into phospholipid bilayers reflects the polarity of the in situ TC. We consider it unlikely that K accumulation into TC during tetanus may have been obscured by volume changes due to water movements or lost through freeze-drying for the following reasons: (a) there was no significant swelling or shrinkage of the TC profiles in freeze-substituted material and the TC/cytoplasmic dry mass ratio (as reflected in continuum counts) was unchanged during tetanus; (b) sharp in vivo ionic gradients across cell membranes are preserved during rapid freezing, cryoultramicrotomy and drying (35,96, and our study), even in intracellular vacuoles (32,96) ; (c) the gain in Mg content of the TC during tetanus was readily demonstrable, although it should be negligible compared to K uptake if the respective permeabilities, as measured in isolated preparations, dominated the influx mechanisms; and (d) the gain in K in the TC during K contracture was preserved by the preparative cryotechniques (our study) as were comparable changes in mitochondria and in nuclei in vascular smooth muscle (89). The magnitude and sign of the electrical potential across the SR membrane has considerable bearing on the mechanism of Ca release.…”
Section: Calcium Release and Other Changes In The Composition Of The mentioning
confidence: 99%